Issues in Learning Mathematics in Senior Grades of Elementary School and Possible Solutions in the Context of Didactic-Methodical Procedures - Vučinić, Dragiša S. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
It is generally known that mathematical knowledge takes on an increasing importance in the society today. Furthermore, mathematics finds its application in almost all scientific and practical activities. In relation to that, it is justifiable to argue that quality education in the field of mathematics is one of the basic conditions for the professional and academic progress of each student. However, the results of various surveys indicate that mathematics is one of the least favourite subjects and has the lowest score among the pupils in higher grades of elementary school. Heaving in mind the importance of mathematical education, this paper considered various problems and difficulties which senior elementary students are facing in the course of learning mathematics. In accordance with the significant role of a teacher as one of the key factors in the quality educational process, the paper points to the possibility of overcoming certain problems in the context of didactic-methodical procedures of mathematics teachers.